A música como arte imitativa: da estética cartesiana à arte de expressar paixões - Sahd, Luiz Felipe Netto de Andrade e Silva (2019)
The Quarrel of the Buffoons, which lasted from 1752 to 1754, and set the French operatic tradition against the Italian, serves as a backdrop to the article. Rameau was accused of being outdated, and his music too complicated, compared to the “simplicity” and “naturalness” of Pergolesi’s La Serva Padrona comic. In the mid- -1750s Rameau criticized the music entries Rousseau had written for the Encyclopédie, leading to a dispute with philosophers D’Alembert and Diderot.